The Bumiputera Policy - Dynamics and Dilemma: The Orang Ulu Perspectives - Francis J. Lian, (Kajian Malaysia, 2003)
Who are the 'Orang Ulu'? The term 'Orang Ulu' is not a legal term and no such racial group is listed in the Malaysian constitution. It is a term politically coined to group together 27 very small but ethnically diverse groups in Sarawak with a population ranging from less than 300 persons to over 25,000 persons. Together they totalled approximately 150,000 persons (0.04% of Malaysian population in 2000). In the state of Sarawak, they are the fifth largest of the minority groups after the Iban, Chinese, Malay and Bidayuh. The other minority groups are the Melanaus and Indians.